Stratification of Candidates for Induction Chemotherapy in Stage III-IV Nasopharyngeal Carcinoma: A Large Cohort Study Based on a Comprehensive Prognostic Model - Sun, Xue-Song; Xiao, Bei-Bei; Lu, Zi-Jian; Liu, Sai-Lan; Chen, Qiu-Yan; Yuan, Li; Tang, Lin-Quan; Mai, Hai-Qiang (Frontiers in Oncology, 2020)
Objective: To establish a prognostic index (PI) for stage III-IV nasopharyngeal carcinoma (NPC) patients to personalize recommendations for induction chemotherapy (IC) before intensity-modulated radiotherapy (IMRT). Patients and Methods: The current study involved 3586 patients diagnosed with stage III-IV NPC. Patients received concurrent chemoradiotherapy (CCRT) with or without IC. Factors used to construct the PI were selected by a multivariate analysis of progression-free survival (PFS), the primary endpoint (P < 0.05). The cutoff value of PI was determined by the receiver operating characteristic curve. Results: Five variables were selected based on a backward procedure in a Cox proportional hazards model: gender, T stage, N stage, lactate dehydrogenase (LDH), and Epstein–Barr virus (EBV) DNA. The cutoff value of PI was 0.8. The high-risk subgroup showed worse outcomes than the low-risk subgroup on all endpoints: PFS, overall survival (OS), locoregional relapse–free survival (LRFS), and distant metastasis–free survival (DMFS). In the low-risk subgroup (PI < 0.8), patients showed comparable survival outcomes on all clinical endpoints regardless of IC application, whereas in the high-risk subgroup (PI > 0.8), the addition of IC significantly improved PFS, OS, and DMFS, though not LRFS. According to multivariate analyses, IC was a protective factor for PFS, OS, and DMFS in the high-risk subgroup, while it had no significant benefit in the low-risk subgroup. Conclusion: The new prognostic model effectively stratifies patients with stage III-IV NPC. High-risk patients are candidates for IC before CCRT, while low-risk patients are unlikely to benefit from it.